USABILITY ANALYSIS ON THE ZEE STUDIO WEBSITE USING HEURISTIC EVALUATION - Davit Hermawan Davit; Nurdiansyah Permana; Fikri Emsa Silmi (Politeknik Mardira Indonesia, 2025)
Usability is an essential prerequisite for a website, serving as a benchmark for system feasibility based on effectiveness, efficiency, and user satisfaction in a given context. In the context of digital marketing and creative services, the quality of the user experience is a key determinant of platform success. This study aims to assess the usability level of the Zee Studio website, identifying potential user interaction issues that may hinder the achievement of business goals and customer satisfaction. Neglected usability issues on a platform can negatively impact the user experience, ultimately reducing efficiency and satisfaction. Therefore, the Heuristic Evaluation method was chosen as the primary instrument in this study. The evaluation was conducted by experts who reviewed the user interface based on Jakob Nielsen's ten heuristic principles to identify heuristic violations in website design. The results of this study are expected to provide a comprehensive list of detected usability issues, complete with severity levels and specific recommendations for improvement. The primary contribution of this research is improving the quality of the Zee Studio website, making it more effective in conveying information, more efficient in navigation, and able to provide optimal levels of satisfaction for its users.